Correlation of initial blast and minimal residual disease with biological characteristics of acute leukaemia. - Tay, Siow Phing; Henry Rantai, Anak Gudum (College of Pathologists, Academy of Medicine, Malaysia, 2019)
Introduction: Acute leukaemias (AL) are highly malignant neoplasms and responsible for a large number of haemopoietic cancerrelated deaths. Prognosis of AL is dependent upon various biological and clinical factors. There is growing body of evidence that supports minimal residual disease (MRD) values and initial blast count (IBC) at diagnosis in predicting treatment outcome and relapse risk in AL. However, there is scarcity of data on the relationship of IBC and MRD with biological characteristics [gender, age groups, AL types and immunophenotypic aberrancy (IA)]. Therefore, this study was designed to determine the correlation of IBC, MRD (post-induction chemotherapy) and biological characteristics of AL. Materials & Methods: This was a retrospective study involving all the 493 AL patients diagnosed at the Flow Cytometry Laboratory of UNIMAS from 2006 to 2014. Results & Discussion: The AL patients comprised 44.2% children and 55.8% adults with a male predominance (55.6%). The mean ages for children and adults were 5 and 45 years old, respectively. There were more AML (55.2%) than ALL (44.8%) cases. B-ALL and AML-M2 predominated the AL subtypes in children and adults, respectively. ALL patients showed significantly higher IBC (p£0.001) and MRD (p£0.001) levels than AML. Significantly higher IBC (p£0.001) and lower MRD (p=0.014) levels were observed in children, indicating a better response to treatment, as compared to adults. However, there was no significant difference in IBC and MRD found between genders. In addition, expression of IA was more common in AML than ALL (p=0.037). Conclusions: To the best of our knowledge, this was the first report of a significant negative correlation between IBC and MRD (r=-0.24, p=0.001), whereas IBC and MRD did not correlate significantly with IA. As MRD studies were more routinely performed in ALL, these findings reflected the successful management of ALL patients in our local clinical settings. Future studies should be embarked to further assess the value of IBC, MRD and IA in prognosticating the disease outcome among the local AL patients.